ChemInform Abstract: Contribution of Heterobifunctional Ligands to Transition Metal‐Catalyzed C—C Coupling Reactions. Issue 19 (April 2016) - Labande, Agnes; Deydier, Eric; Manoury, Eric; Daran, Jean‐Claude; Audin, Catherine; Poli, Rinaldo
Abstract: Review: 67 refs.